Avian Macrophage Responses to Virulent and Avirulent Clostridium perfringens - Raveendra R. Kulkarni; Carissa Gaghan; Javid Mohammed (Pathogens, 2022)
The present study evaluated the avian macrophage responses against Clostridium perfringens that varied in their ability to cause necrotic enteritis in chickens. Strains CP5 (avirulent-netB+), CP1 (virulent-netB+), and CP26 (highly virulent-netB+tpeL+) were used to evaluate their effect on macrophages (MQ-NCSU cells) and primary splenic and cecal tonsil mononuclear cells. The bacilli (whole cells) or their secretory products from all three strains induced a significant increase in the macrophage transcription of Toll-like receptor (TLR)21, TLR2, interleukin (IL)-1β, inducible nitric oxide synthase (iNOS), and CD80 genes as well as their nitric oxide (NO) production and major histocompatibility complex (MHC)-II surface expression compared to an unstimulated control. The CP1 and CP26-induced expression of interferon (IFN)γ, IL-6, CD40 genes, MHC-II upregulation, and NO production was significantly higher than that of CP5 and control groups. Furthermore, splenocytes and cecal tonsillocytes stimulated with bacilli or secretory products from all the strains showed a significant increase in the frequency of macrophages, their surface expression of MHC-II and NO production, while CP26-induced responses were significantly higher for the rest of the groups. In summary, macrophage interaction with C. perfringens can lead to cellular activation and, the ability of this pathogen to induce macrophage responses may depend on its level of virulence.